Characterization of Municipal Solid Waste for Useful Energy Application in Mbeya City (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
Municipal solid waste (MSW) management has emerged as one of the challenges facing environmental protection authorities in developing countries, Tanzania inclusive. This paper presents a characterization study of the MSW generated in Mbeya City, Tanzania. The characteristics of the MSW were determined in terms of the components' percentage of mass (kg) and physical and chemical properties. The study was designed to examine the potential of MSW as a feedstock for energy recovery processes. A study in Mbeya City found that food, organic, paper, plastic, and nylon waste constitute a significant portion of municipal solid waste (MSW), with over 62.4% being organic and food waste. The study found that food waste can be used as a feedstock in anaerobic digestion plants to produce biogas and biofertilizer compost. The study also found that waste with higher carbon and hydrogen content is suitable for thermochemical waste-to-energy processes. Understanding MSW is crucial for effective waste management strategies and promoting a circular economy.